Brain metabolic changes in patients with disseminated malignant melanoma under immunotherapy. Issue 5 (15th June 2022) - Sizova, Marina; Camacho, Valle; Sampedro, Frederic; Sabaté-Llobera, Aida; Abouzian, Safae; Stefaneli, Patricia; Duch, Joan; Fernández-León, Alejandro; López-Mora, Diego Alfonso; Estorch, Montserrat; Carrió, Ignasi; Flotats, Albert
Abstract : Although there is evidence that chemotherapy can have side effects on metabolism and brain function, there are few studies on the occurrence of these side effects with immunotherapy. The present study was conducted to assess whether brain metabolic changes occur in patients with malignant melanoma under immunotherapy. Thirty-nine patients after surgical intervention and with a diagnosis of malignant melanoma were retrospectively included and were divided into two groups: one group under the first-line therapy with anti-programmed cell death-1 ± anti-cytotoxic T lymphocyte antigen-4 monoclonal antibodies and the other group without any treatment after surgery, which served as a control. Basal and follow-up whole body and brain 2-[ 18 F]fluoro-2-deoxy-D-glucose ( 18 F]FDG) PET/computed tomography (CT) studies were performed. Changes in brain glucose metabolism after treatment initiation of the immunotherapy group were compared with the findings in the control group. In addition, longitudinal regression analysis to investigate whether the time under immunotherapy influenced the changes of brain metabolism was performed. None of the patients presented cognitive impairment or other neurological alterations between basal and follow-up brain [ 18 F]FDG PET/CT examinations. The statistical analysis revealed a significant relative SUV (SUVr)-loss in the left frontal region in patients of the immunotherapy group compared with the control group, with r adjusted = −0.62 and P = 0.008. Severity of SUVr-loss was correlated with duration of treatment. Patients with disseminated malignant melanoma receiving immunotherapy may present a decrease of brain metabolism in the left frontal region, which is related with time-under-treatment, without any clinical evidence of neurological disorder.